Calcareous nannoplankton response to the latest Cenomanian Oceanic Anoxic Event 2 perturbation - G. Faucher; E. Erba; C. Bottini; G. Gambacorta (Università degli studi di Milano. Dipartimento di Scienze della Terra "A. Desio", 2017)
Morphometric analyses were performed on Biscutum constans, Zeugrhabdotus erectus, Discorhabdus rotatorius and Watznaueria barnesiae specimens from five sections spanning the Cenomanian-Turonian boundary interval including Oceanic Anoxic Event (OAE) 2 (similar to 94 Ma). The study provides evidence for size fluctuations and dwarfism of B. constans during OAE 2, followed by a partial recovery at the end of the event: this taxon appears to be the most sensitive species, with similar and coeval size trends in all the analyzed sections. Conversely, morphometry shows negligible or unsystematic coccolith variations in Z. erectus, D. rotatorius and W. barnesiae. The comparison of OAE 2 data with those available for the early Aptian OAE 1a and latest Albian OAE 1d, indicates that B. constans repeatedly underwent size reduction and temporary dwarfism, possibly implying that the same paleoenvironmental factors controlled calcification of B. constans during subsequent OAEs although the amplitude of B. constans coccolith reduction is significantly larger for OAE 1a than OAE 2. Paleoceanographic reconstructions suggest that ocean chemistry related to the amount of CO2 and toxic metal concentrations played a central role in B. constans coccolith secretion, while temperature and nutrient availability do not seem to have been crucial. Contrary to OAE 1a, Z. erectus, D. rotatorius and W. barnesiae appear to be substantially unrelated to OAE 2 paleoenvironmental stress, possibly because of different degrees of perturbation.